The associations between female fecundability and postpartum breastfeeding: A prospective cohort study - Jiuming Li; Xiang Hong; Xiaoqi Zhu; Jingying Wu; Haitao Yang; Xuening Zhang; Bei Wang (PLoS ONE, 2025)
Objective This study aimed to investigate the relationship between women’s fecundability and postpartum breastfeeding. Methods We used a prospective cohort study design to recruit pregnant women who came to the hospital for antenatal checkups before 20 weeks’ gestation between April 2019 and March 2020 at the Maternal and Child Health Hospital of Gulou District, Nanjing, China. Women were categorized into prolonged time to pregnancy (TTP) group (>3 months) and shorten TTP (≤3 months) groups. A telephone follow-up was conducted 42 days postpartum to collect breastfeeding practice data. Logistic regression models were employed to analyze the association between TTP and exclusive breastfeeding. Results A total of 535 pregnant women were initially included in the study cohort and 478(89.35%) completed the follow-up, among 79 (16.5%) in the prolonged TTP group, and the rest in the short TTP group (n = 399, 83.5%). According to the follow-up, 271 (56.7%) were in the exclusive breastfeeding group and the rest in the non-exclusive breastfeeding group (n = 207, 43.3%). A significant decrease in exclusive breastfeeding rate was observed in the prolonged TTP group compared to the short TTP group (OR=0.46, 95% CI: 0.27–0.74). After adjusting for potential confounders such as age, husband’s age, BMI, and regularity of menstruation, the negative association between TTP and exclusive breastfeeding remained (OR=0.50, 95% CI: 0.29–0.84). In stratified analyses, the results were generally consistent. Conclusion The probability of postpartum breastfeeding is lower in women with lower fecundability. These findings suggest that women with lower fecundability may benefit from targeted breastfeeding support.